Sphingolipids: Basic Science and Drug Development - Gulbins, Erich; Petrache, Irina; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
Sphingolipids are lipid components of the plasma membrane in eukaryotic cells. They have an important function in signaling mechanisms in the cell. This book on sphingolipids provides insights into the basics of sphingolipid biology and drug development, with a particular emphasis on the sphingolipid derivative ceramide. In the first part basic functions of sphingolipids are described, as well as the genetics of important enzymes, sphingolipid metabolism and synthesis. The second part of this first volume focuses on drug development and pharmacology. The book is intended for scientists in pharmacology, biochemistry and cell biology with a focus on biomedical research as well as for clinicians working in pharmacology, oncology, cardiology, neurology and infectious disease. Together with Volume 216 by the same editors, the collection represents a unique, comprehensive work on sphingolipids, providing information on both sphingolipids$1 (Bbasic biology (including synthesis, metabolism and cell biology) and their important function in a (patho-)physiological context.s
Preface -- Part 1. Basic mechanisms -- Part 2. Drug development.
Keywords: Medicine; Toxicology; Cytology; Cell membranes; Biomedicine; Pharmacology/Toxicology.; Membrane Biology; Cell Biology; Molecular Medicine